2013
DOI: 10.1007/s10140-013-1173-1
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of facial fractures in motor vehicle accidents: an MDCT study of 374 patients

Abstract: Road traffic accidents are a major health problem worldwide resulting frequently in maxillofacial injuries. The purpose of the study was to assess the incidence and spectrum of facial fractures in patients involved in a motor vehicle accident (MVA). Using picture archiving and communication system, all requests for suspected facial trauma were retrieved during a 62-month period; 374 met the inclusion criteria. Two researchers interpreted the multidetector computed tomography images by consensus. The motor vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
3
15
1
Order By: Relevance
“…The 2 most common subgroups of facial injuries that can be classified as HET injuries are GSWs and high-velocity MVCs, and the most common facial fractures resulting from a high-energy GSW and MVCs are the nasal, orbital, maxillary, zygomatic, and mandibular bones. 8,17,22,23 Prior larger studies have reported both the mandible 6,10 and the zygoma 24 as the most commonly injured maxillofacial bones in GSWs to the face. Based on the geometry of the face, protruding areas are most likely to sustain injury in highenergy MVC.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The 2 most common subgroups of facial injuries that can be classified as HET injuries are GSWs and high-velocity MVCs, and the most common facial fractures resulting from a high-energy GSW and MVCs are the nasal, orbital, maxillary, zygomatic, and mandibular bones. 8,17,22,23 Prior larger studies have reported both the mandible 6,10 and the zygoma 24 as the most commonly injured maxillofacial bones in GSWs to the face. Based on the geometry of the face, protruding areas are most likely to sustain injury in highenergy MVC.…”
Section: Discussionmentioning
confidence: 96%
“…5,16,17 Orbital and nasal fractures commonly occur together in these types of injuries and may accompany high-energy Le-Fort fractures. 8,18 The bone associated with the frontal sinus structure can withstand between 800 and 2200 lb of pressure, and the presence of fractures at this site likely indicates high-energy trauma. 8,18-20 Furthermore, a previous study analyzing force of impact established a resistance to fracture of the frontal bone at 1350 lb of force, compared with the more fragile mandibular and zygomatic bones at 427 and 360 lb of force, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms of injury were most commonly Bstruck by^injuries (e.g., falling objects and sports), falls, and motor vehicle accidents [3]. In motor vehicle accidents, nasal, orbital, and skull base fractures are most common [4], and in patients with falling accidents, zygomatic complex, nasal, and orbital fractures are most common [5]. Facial trauma patients are most commonly evaluated using CT due to its high sensitivity for detection of facial fractures and the ability to detect soft tissue injuries [6,7].…”
Section: Discussionmentioning
confidence: 99%